การพัฒนาคนในระบบการจัดการศึกษาไทย - ทองโปร่ง อำนวย (Ph.D. in Social Sciences Journal, 2017)
การศึกษาเป็นปัจจัยสำคัญในการเรียนรู้ของมนุษย์ ดังนั้นการพัฒนาคนในระบบการจัดการศึกษาจึงมีความจำเป็นอย่างยิ่งต่อการสร้างสรรค์ทรัพยากรมนุษย์ให้เป็นทุนมนุษย์ ที่มีสติปัญญา มีความรู้ เป็นคนดี มีคุณธรรม จริยธรรม และมีความสุข ให้สมบูรณ์พร้อมทั้งร่างกายและจิตใจ ผ่านการจัดการด้านการศึกษาที่มีคุณภาพเพื่อเป็นกำลังในการพัฒนาประเทศ โดยให้เกิดการเรียนรู้ที่จะดำรงชีวิตอย่างมีความสุข พอเพียง และแบ่งปันโดยคำนึงถึงประโยชน์สุขของสังคมและประเทศชาติเป็นสำคัญ รัฐบาลต้องกำหนดวิสัยทัศน์หรือเป้าหมายของการจัดการศึกษาไทยให้ชัดเจน มีขอบเขตแน่นอน ต้องกำหนดคุณลักษณะเด็กไทยที่พึงมี อันเป็นเป้าหมายการสร้างพลเมืองที่มีคุณภาพทางสติปัญญาตามศักยภาพของตน มีทักษะการปฏิบัติงานตรงกับตลาดแรงงาน มีคุณธรรมจริยธรรมที่เหมาะสมใช้ชีวิตที่มีคุณค่าเหมาะสมกับตนเอง ทำงานร่วมกับผู้อื่นได้ กล้าเผชิญกับปัญหา มีเสรีภาพต่อการคิดและการกระทำที่ไม่ละเมิดสิทธิของผู้อื่น และมีความรับผิดชอบต่อการกระทำนั้น มองโลกในแง่ดี มีไมตรีต่อผู้อื่นด้วยจิตใจที่ดีงาม จึงเป็นการปฏิรูปการศึกษาที่พัฒนาคนที่เป็นกำลังคนที่สำคัญของประเทศเพื่อนำไปสู่การพัฒนาที่ยั่งยืน HUMAN DEVELOPMENT OF EDUCATION MANAGEMENT SYSTEM IN THAILAND Education is an important factor of human learning. Therefore, the human development of education management system is the necessary for the human resource creation to be the human capital. The human capitals have intelligence, knowledge, be good person, be moral person which have ethical and happiness. Which completely human in both side of physically and mentally through the quality education management to be the power of the country development in terms of learning to fulfill the living way to happy, enough, and share the others. Taking into account the society and country benefit for the first priority. Government must set a vision or goal of the education management clearly. Setting up the possibility feature of Thai’s children. The goal should be to create the quality citizens of their intellectual potential. The quality citizens have the worked shill according to the labor market. The quality citizens have the moral to live in valuable sense of themselves. Which can collaborate with the others, brave to face of the problems, have freedom to think and act that do not violate the others’ right. There are responsible action, optimistic mind, relations with the others with generosity and spirit. All that’s mean the education reform that is underway to develop the country to contribute to sustainable development.